The Analysis of Mathematical Literacy on Realistic Problem-Based Learning with E-Edmodo Based on Student’s Self Efficacy (Journal of Primary Education, 2017)
This study aims to: (a) analyze the effectiveness of the realistic approach of project-based learning with E-Edmodo as a media, which is proven if the mathematical literacy ability of the experimental class: (1) passes the classical completion as at least 75% of the students reach minimum score of 70; (2) is better than the control class; (3) is increasing, (b) analyze the mathematical literacy ability of the experimental class based on student’s self efficacy. The mixed method was used in this study. The subject of the qualitative study was the students of class VII C (experimental class) and class VII A (control class), while the subjects of the qualitative study were 6 selected students from class VII C consisting of two students each in high, medium, and low self-efficacy groups. The data collection techniques included observation, test, interview and documentation. Based on the data analysis, it can be concluded that: (1) Realistic project-based learning with E-Edmodo was effective, shown by the achievement of classical completion, the average mathematical literacy ability of the experiment class students was higher than the control class, and there was improvement of mathematical literacy ability on Realistic project-based learning with E-Edmodo by 62%. (2) Students with high self-efficacy achieved excellent level of mathematical literacy ability, while students with medium self-efficacy achieved good mathematical literacy ability, and students with low self-efficacy achieved sufficient degree of literacy mathematics ability.